Approach to signal loss in intraoperative nerve monitoring in thyroid surgery questionnaire: a Turkish surgical perspective - Iscan, Yalin; Karatas, Irem; Aygun, Nurcihan; Dural, Ahmet Cem; Teksoz, Serkan; Makay, Ozer; Emre, Ali Uğur; Tunca, Fatih; Uludag, Mehmet; İçöz, Gökhan and Giles Senyürek, Yasemin and Işgör, Adnan and Haciyanli, Mehmet (Frontiers in Endocrinology, 2025)
PurposeThis study aimed to evaluate surgeons’ use of intraoperative nerve monitoring (IONM) during thyroidectomy and their approach to loss of signal (LOS) in various clinical scenarios.Materials and MethodsA survey was conducted by the Turkish Endocrine Surgery Society on members of the Society in February 2020 and consisted of 16 questions. The practice of IONM use, rate of inclusion in informed consent texts, and attitudes of participants in case of signal loss were investigated. The study was conducted with 183 participants between February 4-12, 2020.ResultsMost participants (58.2%) had more than 10 years of surgical experience and 36.6% performed more than 50 thyroidectomies annually. IONM was routinely used by 78.7% of the participants, whereas 16.4% reserved its use in difficult cases. Only 5.2% of the participants performed continuous monitoring. In case-based LOS scenarios, the majority of participants (approximately 60%) terminated the operation when the nerve was anatomically intact but LOS persisted, except in high-risk cancer cases. When the nerve anatomy was disrupted, most participants terminated the surgery, except for the high-risk cancer group. In cases of irreversible LOS with preserved nerve integrity, 58.9% of the patients preferred continuous vagus stimulation on the contralateral side, whereas 41.1% preferred intermittent nerve monitoring. Although 68.2% of the participants verbally informed the patients about the risks of LOS, only 24.4% provided this information on the consent form.ConclusionThe use of IONM in thyroid surgery is increasing in our country. However, there is still no consensus on the approach for staged thyroidectomy in cases of signal loss, and institutional and individual differences persist. Further studies are needed to determine the medical-legal implications and effects of these variations.